Giant Earthquakes Beneath Canada's West Coast - Hyndman, R.; Rogers, G.; Dragert, H.; Wang, K.; Clague, J.; Adams, J.; Bobrowsky, P. (Geoscience Canada, 1996)
Summary Compelling evidence for past great earthquakes along the Cascadia subduction zone and for the present buildup of elastic strain have been revealed through a multidisciplinary research effort. From Vancouver Island to northern California, there is paleoseismic evidence of sudden subsidence of the coast and of strong shaking from huge earthquakes at irregular intervals averaging about 500 years. The last was 300 years ago, before the historical period.Several independent techniques show the present shortening and buckling ofthe coastal region diagnostic of strain accumulation on a locked subduction thrust fault. The pattern of strain and the temperature at depth on the fault allow definition of the maximum landward extent of future events. Although the earthquakes are very large, up to magnitude 9, the predicted ruptures are mainly offshore some distance from the major cities, limiting the severity of the expected shaking.